BERKELEY PHILOSOPHY TO ANSWER THE PROBLEM OF SPIRITUAL CRISIS - Rizky Yazid; Muhammad Negara (Ushuluna: Jurnal Ilmu Ushuluddin, 2023)
This article aims to reflect on the crisis of spirituality in the recovery period after the Covid-19 pandemic through the philosophical views of George Berkeley. The crisis was getting worse because of Russia's war with Ukraine so that it pushed most people to focus on materialistic dimensions solely for the sake of economic recovery. The problem is, during the recovery period, many people separate material things from spiritual things, so they tend to pursue one or the other. In fact, both material and spiritual are the same thing, namely the quality of spirit. The implication is that the material dimension tends to push a person towards materialism in a recovery situation and ignores the spiritual dimension. This study uses a critical reflection method that aims to contemplate the reality of the recovery from the Covid-19 pandemic and assess it epistemically. The findings from this study are that material aspects or qualities are part of spiritual qualities. In other words, following Berkeley, spiritual quality is the scope of the process when a person perceives both the external world (objective reality) and subjective reality simultaneously. This means that Berkeley's theory of philosophy of perception as a philosophical viewpoint is still relevant for understanding reality in the midst of a spiritual crisis after the global recovery of the Covid-19 pandemic.